Physicians Report Sleep Apnea Infrequently in Older and Older Vulnerable Adults. Issue 9 (4th May 2017) - Namen, Andrew M.; Forest, Daniel J.; Huang, Karen E.; Feldman, Steven R.; Hazzard, William R.; Peters, Stephen P.; Haponik, Edward F.
Abstract : Objectives: To determine how often outpatient physician visits detect sleep apnea (SA) in older persons in the United States. Design: Retrospective Analysis. Setting: US non hospital and hospital based clinics. Participants: US physicians. Measurements: National Ambulatory Medical Care Survey and National Hospital Ambulatory Medical Care Survey data from 1993 to 2011 were used to assess the frequency of physicians' coding diagnoses of SA in persons aged 65 and older. Which specialties are most likely to report SA, the most‐common comorbid conditions reported with SA, and the likelihood of reporting SA in patient visits for dementia and preoperative care were assessed. Results: From 1993 to 2011, physicians reported SA in 0.3% of all office visits in persons aged 65 and older. SA reported in visits increased from 130, 000 in 1993 to 2, 070, 000 in 2011, with an annual per capita visit reporting rate of 0.07% to 0.74%. In older populations, the proportion of documented SA visits by specialists rose, and that of primary care providers decreased. Older adults with a diagnosis of SA had higher average number of comorbidities than those without SA (1.8 vs 1.3). Reporting SA was low in visits with a diagnosis of dementia and classified as a preoperative visits. Conclusion: In two nationwide surveys, SA reporting by physicians in elderly adults was 16 as greater in 2001 as in 1993, although reporting of SA remains infrequent (<1% of visits) even in vulnerable populations.